FISCAL AUTONOMY AND REVENUE GROWTH: THE IMPORTANCE OF SPATIAL CONTEXT IN LOCAL GOVERNMENT REFORM - Edem Lekettey; Nugraha, Nugraha; Maya Sari; Denny Andriana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the revenue growth performance of Ghana's Metropolitan, Municipal, and District Assemblies (MMDAs) and explores the moderating influence of population density on the relationship between financial autonomy and revenue growth. This study analyzes the impact of institutional capability and spatial context on subnational fiscal performance in the context of Ghana's decentralization, based on fiscal federalism and institutional theory. Auditor-General's Reports and the Ghana Statistical Service provided data on 261 MMDAs from 2018 to 2023. Stata 18 and R 4.3 were used for fixed-effects estimation, the system generalized method of moments (GMM), robustness testing, and moderation analysis using Hayes' PROCESS Model 1. The results indicate that financial autonomy substantially improved subnational revenue growth (β = 0.0036, p < 0.001). Population density did not significantly reduce this association (β = -0.0031, p = 0.108). Further analysis indicates that the fiscal benefits of autonomy are more pronounced in low-density assemblies, suggesting that institutional and administrative efficiencies play a more critical role in fiscal performance than population size. The findings indicate that decentralization reforms should prioritize improving governance quality, institutional discipline, and fiscal accountability, rather than demographic or spatial considerations. This study represents the first application of moderated panel models to 261 Ghanaian MMDAs, demonstrating that institutional strength, rather than population density, serves as the principal determinant of fiscal benefits from autonomy in developing countries. This finding contributes to the discussion on fiscal federalism and institutional theories.